Performance of BAT Algorithm on Localization of Wireless Sensor Network - Goyal, Sonia; Patterh, Manjeet Singh (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Many applications of wireless sensor networks (WSN) require information about the geographical location of each sensor node. Devices that form WSN are expected to be remotely deployed in large numbers in a sensing field, and to self -organize to perform sensing and acting task. The goal of localization is to assign geographical coordinates to each device with unknown position in the deployment area. Recently, the popular strategy is to apply optimization algorithms to solve the localization problem. In this paper, the bat algorithm is implemented to estimate the sensor‟s position.